Knowledge, Beliefs and Attitudes towards AIDS among Intermediate and Secondary School Teachers; Baghdad - Abed, *Baqir Kareem; Abdul-Rahim, Yousif; Fathalla, Mural Morad (AL-Kindy College Medical Journal, 2008)
Back ground: AIDS is considered a dreaded disease.According to recent estimates, 42 million people sufferfrom HIV/AIDS (90% of these being in the developingcountries), with 5 million people newly infected with HIVand 3.1 million deaths in the year 2002 globally. Atpresent, there is no effective vaccine to prevent thedisease. Hence, Health education (Information, Educationand Communication) activities bringing about behavioralchanges in the community, promoting healthy sexualbehavior and preventing the risky ones is the best possiblesolution to the problem of AIDS.Objectives: To find out the knowledge, beliefs andattitudes regarding various aspects of HIV/AIDS amongstintermediate and secondary school teachers in Baghdad. Methods: For this cross-sectional study, we randomlyselected 48 intermediate and secondary schools coveringthe 6 educational directorates in Baghdad, and 642teachers serving in these schools were selected to answerthe questionnaire containing different statementsconcerning basic knowledge of the humanimmunodeficiency virus (HIV) and AcquiredImmune Deficiency Syndrome (AIDS).Results: Revealed an intermediate overall awarenessabout HIV/AIDS.Conclusions: Study highlights the need for teaching theproper aspects of HIV/AIDS curriculum in Iraqi schools.